2020
DOI: 10.3389/fpls.2020.580753
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compound Induction in Plant-Microbe and Plant-Insect Interactions: A Meta-Analysis

Abstract: Plants rely on a variety of ways to protect themselves from being fed upon, including de novo production of specific compounds such as those termed as phenolics. Phenolics are often described as important in plant health and numerous studies have concluded they increase as a result of insect feeding, pathogen infection, or beneficial microorganism colonization. However, there are some studies reaching differing conclusions. Therefore, meta-analyses were conducted to observe whether common trends in phenolic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 78 publications
3
61
0
Order By: Relevance
“…The effect of pathogens in the absence of genetic mechanisms of resistance is probably associated with the induction of phenolic compound accumulation and activation of the corresponding metabolic pathways. A metaanalysis confirmed that the total phenolic content increases in response to infection with bacterial and fungal microorganisms, as well as insects [17]. Among the studied hybrids with high levels of phenolics and flavonoids, significant differences in their resistance to phytopathogens were observed.…”
Section: Total Phenolic and Flavonoids Contents Estimationmentioning
confidence: 65%
“…The effect of pathogens in the absence of genetic mechanisms of resistance is probably associated with the induction of phenolic compound accumulation and activation of the corresponding metabolic pathways. A metaanalysis confirmed that the total phenolic content increases in response to infection with bacterial and fungal microorganisms, as well as insects [17]. Among the studied hybrids with high levels of phenolics and flavonoids, significant differences in their resistance to phytopathogens were observed.…”
Section: Total Phenolic and Flavonoids Contents Estimationmentioning
confidence: 65%
“…m/z 771.1039; error, 0.7 ppm). Modification of phenolic compounds in fungus gardens has been described as a mechanism of detoxifying these common plant defenses against defoliating herbivores ( 6 , 20 , 50 , 51 ). Additionally, gallic acid (compound 5) can be produced by endophytic microorganisms ( 52 ), suggesting another interesting source of these phenolic derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The root exudated phenolics were higher in concentration initially and diminished laterally. Microbial-mediated induction of root exudates is well documented ( Wallis and Galarneau, 2020 ). As reported by Jayapala et al (2019) , rhizobacteria induced a higher phenolic acid concentration in chili ( Capsicum annum ) on the 5th day of post-inoculation (dpi).…”
Section: Discussionmentioning
confidence: 99%